Informed Consent sebagai Dasar Persetujuan Dalam Perjanjian Terapeutik Terminasi Kehamilan - Dian Wiris Woro Wardani; Rizki Tri Anugrah Bhakti; Alwan Hadiyanto (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the legal position of informed consent as the basis for the validity of therapeutic agreements in the termination of pregnancy and to examine the legal consequences of negligence within the framework of health law. The study is grounded in the high medical risk associated with pregnancy termination and the persistence of normative issues concerning the standards of valid consent, potential disharmony in emergencies, and the lack of systematic integration among constitutional, contractual, and legal accountability dimensions. This research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that informed consent constitutes a substantive juridical requirement that determines the legality of medical procedures, limits the authority of healthcare professionals, and serves as the basis for determining civil, administrative, and criminal liability based on compliance with professional standards and causal relationships. Accordingly, the legal validity of therapeutic termination of pregnancy is not determined by administrative formalities, but by the fulfillment of substantively valid consent. The novelty of this research lies in the formulation of an integrative conceptual framework that links the constitutional legitimacy of the right to health, the structure of therapeutic agreements, and the regime of legal accountability within a unified normative system. Penelitian ini bertujuan menganalisis kedudukan informed consent sebagai dasar keabsahan perjanjian terapeutik dalam terminasi kehamilan serta menilai konsekuensi hukum kelalaiannya dalam kerangka hukum kesehatan. Kajian ini dilatarbelakangi oleh tingginya risiko medis terminasi kehamilan dan masih adanya persoalan normatif terkait standar persetujuan yang sah, potensi disharmoni dalam kondisi kegawatdaruratan, serta belum terintegrasinya dimensi konstitusional, kontraktual, dan pertanggungjawaban hukum secara sistematis. Penelitian menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa informed consent merupakan syarat yuridis substantif yang menentukan legalitas tindakan medis, membatasi kewenangan tenaga kesehatan, serta menjadi dasar penentuan tanggung jawab perdata, administratif, dan pidana berdasarkan kepatuhan terhadap standar profesi dan hubungan kausal. Dengan demikian, keabsahan terminasi kehamilan terapeutik tidak ditentukan oleh formalitas administratif, melainkan oleh terpenuhinya persetujuan yang sah secara substantif. Kebaruan penelitian terletak pada perumusan kerangka konseptual integratif yang menghubungkan legitimasi konstitusional hak kesehatan, struktur perjanjian terapeutik, dan rezim pertanggungjawaban hukum dalam satu sistem normatif terpadu.